2017
DOI: 10.1186/s40529-017-0182-x
|View full text |Cite
|
Sign up to set email alerts
|

Three new species of Begonia sect. Baryandra from Panay Island, Philippines

Abstract: BackgroundThe flora of Panay Island is under-collected compared with the other islands of the Philippines. In a joint expedition to the island, botanists from Taiwan and the Philippines found three unknown Begonia species and compared them with potentially allied species.ResultsThe three species are clearly assignable to Begonia sect. Baryandra which is largely endemic to the Philippines. Studies of literature, herbarium specimens, and living plants support the recognition of the three new species: Begonia cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Although chromosome cytology has only been investigated in 16 species of Begonia sect. Baryandra, a great variation in chromosome numbers of 2n=26, 28, 30, 32, 44 and 56 has been reported (Legro and Doorenbos 1969, 1971, Doorenbos et al 1998, Kokubugata and Madulid 2000, Oginuma and Peng 2002, Hughes et al 2011, Nakamura et al 2013, Rubite et al 2014, Peng et al 2015a, 2017, suggesting that chromosomal changes could have been the major driving force for the generation of high species diversity in the section. However, because their chromosomes are small and generally short ( 2 µm long), karyotypes of sect.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Although chromosome cytology has only been investigated in 16 species of Begonia sect. Baryandra, a great variation in chromosome numbers of 2n=26, 28, 30, 32, 44 and 56 has been reported (Legro and Doorenbos 1969, 1971, Doorenbos et al 1998, Kokubugata and Madulid 2000, Oginuma and Peng 2002, Hughes et al 2011, Nakamura et al 2013, Rubite et al 2014, Peng et al 2015a, 2017, suggesting that chromosomal changes could have been the major driving force for the generation of high species diversity in the section. However, because their chromosomes are small and generally short ( 2 µm long), karyotypes of sect.…”
mentioning
confidence: 96%
“…Subsequent botanical explorations and taxonomic studies revealed additional diversity of sect. Baryandra across the Philippines (e.g., Rubite et al 2014, 2018, Tandang et al 2016, Peng et al 2017, Magtoto et al 2018, Calaramo et al 2019, Pranada et al 2019, Rule et al 2020, drastically increasing the section to 78 species up to date (Hughes et al 2015 onward: https://padme.rbge. org.uk/Begonia/home).…”
mentioning
confidence: 99%
“…ecosystems (FFI 2001). The interest in this component of the biota is growing rapidly, partly because a range of particularly exotic and often attractive plants, such as orchids, begonias (Peng et al 2015(Peng et al , 2017Phutthai and Hughes 2017) and pitcher plants are included in karst flora (Hamilton-Smith 2001). The unusual soil condition paved the way for the high environmental heterogeneity found within forests over limestone (Pérez-García et al 2009).…”
mentioning
confidence: 99%
“…7a) of the University of the Philippines Manila and Mark Hughes (Fig. 7b) of the Royal Botanic Garden Edinburgh that led to the discovery of many new species (e.g., Peng et al 2017;Hughes et al 2018;Rubite et al 2018), the recircumscription of Begonia sect. Baryandra (Rubite et al 2013), phylogeographic (Nakamura et al 2012(Nakamura et al , 2014 and biogeographic (Hughes et al 2015a, b) studies of the section, and the detection of the first hybrid Begonia in the Philippines (Liu et al 2019).…”
Section: Ching-i Peng's Pursuit Of Begoniamentioning
confidence: 99%
“…He and his collaborators described 98 taxa of Begonia new to science (Additional file 3), greatly improving our understanding of the diversity of Asian Begonia. His exquisite taxonomic works of Begonia, always featuring superb illustrations, high-quality colored photographs taken both in the field and studio, and chromosome cytology (e.g., Peng et al 2017;Tseng et al 2017;Hughes et al 2018), have set a very high standard for the systematic study of Asian Begonia, contributing greatly to the resurgence and recent renaissance of Begonia discoveries (e.g., Pham et al 2019;Wang et al 2019). Utilizing BRCAS's Begonia b, d, f, g, h, i, j, k, l, n, and o were taken in Academia Sinica living collection, Dr. Peng and collaborators pioneered chromosome cytology (Peng and Chen 1991;Peng and Sue 2000;Oginuma and Peng 2002;Kono et al 2012a) and in vitro cultivation (Hu et al 2010) in Begonia and conducted novel experiments to understand the nature of leaf variegation (Sheue et al 2012) and iridescence in the genus (Pao et al 2018).…”
Section: Ching-i Peng's Pursuit Of Begoniamentioning
confidence: 99%